2003
DOI: 10.1590/s1519-566x2003000400020
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de plantas daninhas e do algodoeiro no desenvolvimento, reprodução e preferência para oviposição de Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae)

Abstract: This study investigated the effects of six weeds [Amaranthus hybridus L., Desmodium tortuosum (Sw.), Euphorbia heterophylla L., Ageratum conyzoides L., Bidens pilosa L., Ricinus communis L.] and the cotton plant Gossypium hirsutum L. CNPA Precocious 1 on Podisus nigrispinus (Dallas) life history characteristics and oviposition behavior. The study begun with P. nigrispinus eggs placed on plants and caged throughout up to female death. Egg production and selected plant for oviposition by P. nigrispinus were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 13 publications
1
25
0
4
Order By: Relevance
“…This seemed to be the most critic instars for the development of Pentatomidae predators which was also found for P. nigrispinus with different diets (Zanuncio et al, 1996) and Supputius cincticeps (Stal, 1860) (Heteroptera: Pentatomidae) exposed to environmental stresses . The duration of the instars of P. nigrispinus was longer with NaCl or amino acid solutions than that reported for this predator fed on different prey in the presence or absence of plants (Zamperline et al, 1992;Lemos et al, 2001Lemos et al, , 2003Evangelista Jr. et al, 2003). This showed that the development of predators could be affected by the type and quality of prey and the dietary supplement to them (Strohmeyer et al, 1998).…”
Section: Discussionmentioning
confidence: 68%
“…This seemed to be the most critic instars for the development of Pentatomidae predators which was also found for P. nigrispinus with different diets (Zanuncio et al, 1996) and Supputius cincticeps (Stal, 1860) (Heteroptera: Pentatomidae) exposed to environmental stresses . The duration of the instars of P. nigrispinus was longer with NaCl or amino acid solutions than that reported for this predator fed on different prey in the presence or absence of plants (Zamperline et al, 1992;Lemos et al, 2001Lemos et al, , 2003Evangelista Jr. et al, 2003). This showed that the development of predators could be affected by the type and quality of prey and the dietary supplement to them (Strohmeyer et al, 1998).…”
Section: Discussionmentioning
confidence: 68%
“…Nesse sentido, o uso de herbicidas é prática comum, em razão do menor custo e da maior eficiência de controle (Rizzardi et al, 2004). Contudo, a diversidade dessas plantas daninhas em campo pode ser um importante fator para o estabelecimento e a dinâmica de inimigos naturais de pragas, onde esses insetos usufruem dessas plantas para refúgio e sobrevivência (Evangelista Jr. et al, 2003). Os herbicidas atrazine e nicosulfuron são produtos usados atualmente em razão do baixo custo e seletividade à cultura (Rizzardi et al, 2004), sendo recomendados, respectivamente, para controle de plantas daninhas de folhas largas e gramí-neas (Brasil, 2010).…”
Section: Introductionunclassified
“…This includes pollen consumption for those with chewing mouthparts and water and minerals for sucklings (Evangelista Jr. et al, 2004). Several reports show that the quality of the host plant can improve development, fertility, size, survival and population density of non-strictly zoophagous natural enemies (Awmack e Leather 2002; Evangelista et al, 2003Evangelista et al, , 2004. Moreover, zoophytofagy allows predator insects to survive in the field in conditions of prey shortage (Coll e Guershon 2002;De Clercq 2002).…”
Section: Natural Enemies and Their Important Role In Agroecosystemsmentioning
confidence: 99%
“…Predator Podisus nigrispinus Dallas (Hemiptera: Pentatomidae) has benefited from extra food supply provided by plants Ageratum conyzoides L., Amaranthus hybridus L. and B. pilosa. These weeds present in cotton favor colonization and maintenance of P. nigrispinus (Evangelista Jr. et al, 2003).…”
Section: Weed Plants Are a Habitat For Natural Enemies In Agroecosystemsmentioning
confidence: 99%
See 1 more Smart Citation